ASSESSMENT OF HEALTHCARE PROVIDER’S OPINION ABOUT SYMPTOMS & COMPLICATIONS OF PCOs: A MULTICENTERED STUDY - Maimoona Ahmad; Sana Ahmed; Imran Masood; Madeeha Ali; Ayesha Tariq; Komal Farooq (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Polycystic Ovary Syndrome (PCOS) is a complex endocrine disorder with wide-ranging symptoms and complications, necessitating comprehensive understanding among healthcare providers for effective management. This multi-centered, cross-sectional study aimed to assess healthcare providers’ awareness of PCOS symptoms, complications, and management strategies, while exploring the association between their knowledge and education levels. Conducted across six cities in Punjab, Pakistan, the study included 420 healthcare providers from various specialties. A validated, self-designed questionnaire was used to evaluate awareness, with scores categorized as inadequate, moderate, or adequate. The results revealed varying levels of awareness among respondents. While common symptoms like menstrual irregularities and weight gain were widely recognized, less common symptoms such as frontal hair loss and sleep difficulties showed lower awareness. Complications like infertility and psychological disturbances were acknowledged, but gaps remained in understanding long-term risks such as cardiovascular disease. Management strategies like the use of oral contraceptives demonstrated a strong association with education (p<0.001), while lifestyle interventions such as dietary modifications showed mixed results. The mean scores for complications, total awareness, and management were 5.12 (±0.899), 19.44 (±2.172), and 5.42 (±0.849), respectively, indicating moderate overall knowledge with room for improvement. The study highlights the need for targeted educational interventions to address knowledge gaps, particularly in recognizing less common symptoms and implementing holistic management approaches. By enhancing healthcare providers’ understanding of PCOS, this research contributes to improved patient care and outcomes. Future studies should focus on developing standardized training programs and guidelines to ensure comprehensive and evidence-based management of PCOS.